Characterization of clock proteins in the substantia nigra and subthalamic nucleus of the Sapajus apella primate - Guissoni Campos, Leila Maria; Campanari, Gyovanna Sorrentino dos Santos; Santiago, Jeferson; Santos, Eduardo Vinicius Barboza; Santos, Alana Cristy Ghiraldelli; Cabrini, Mayara Longui; Audi, Mauro; Costa, Isabela Bazzo; Evangelista de Araujo, Viviane Canhizares; Bodra, Stephannie Monaco; Gualassi, Maressa Monteiro Pereira; Motta-Teixeira, Lívia Clemente; et al. (Frontiers in Neuroanatomy, 2024)
Clock genes, which are essential for suprachiasmatic nucleus (SCN) function, also play critical roles in other brain regions, and their expression have been the subject of various studies. An increasingly deeper understanding of the expression of these genes in different species contributes to our knowledge of their functions and the factors influencing their expression. Considering that most studies have been conducted in nocturnal rodents, in this study we investigated the presence of Per1, Per2 and Cry1 in neurons of the substantia nigra (SN) and subthalamic nucleus (STN) in a diurnal primate. The immunoreactivity of Per1, Per2, and Cry1 was analyzed using immunohistochemistry, revealing significant Per1-IR, Per2-IR, and Cry1-IR in the SN. While Per1-IR and Per2-IR were also observed in the STN, no Cry1-IR staining was detected in the STN. These results confirm the presence of proteins that regulate circadian rhythms in areas associated with motor behavior.